Amphibian diversity across an urban gradient in southern South America - Demartín, Rocio Pamela; Ghirardi, Romina; López, Javier Alejandro (Frontiers in Ecology and Evolution, 2024)
Habitat alteration is recognized as one of the most important drivers of biodiversity decline. Urbanization implies a major habitat alteration and its impact on biodiversity depends on type and degrees of habitat modifications. Growing cities generate great heterogeneity with respect to the uses of space that enable the preservation of a certain diversity of amphibians within the urban frame. Our objective is to understand how environments with different levels of urbanization influence local amphibian diversity. We grouped various urban green spaces of a medium-sized and growing city of Argentina in relation to natural and anthropic environmental variables which allows us to describe an urban environmental gradient and we calculate beta diversity among these groups of urban environments considering the richness, composition and abundance of amphibian at each sites’ group. From this, we analyze and tested the differences in the functional diversity of amphibians in the defined urban environmental gradient. We hypothesize that: (i) the described spatial heterogeneity would be related to an elevated beta diversity of amphibians within the urban frame; and (ii) the analysis of functional diversity would reveal a stronger biotic or abiotic filtering of the focal community. We found that groups of urban environments with an intermediate degree of urbanization can present a greater functional diversity and species richness than those that are less urbanized. We identified urban avoiders (T. typhonius, P. santafecinus and P. biligonigerus) and urban tolerant species (E. bicolor, R. arenarum, R. dorbignyi, L. macrosternum, L. latinasus, P. albonotatus, D. nanus and S. nasicus). The replacement beta diversity recorded indicated that the species assemblage changes throughout urban environmental gradient, but functionally similar species thrive in the less to the most urbanized sites, allowing them to occupy the entire functional space of the groups of urban environments with different types and degrees of urbanization.